PENGARUH PERSEPSI HARGA DAN PROMOSI TERHADAP MINAT BELI UNKNOWN CASH (UC) DALAM GAMES PLAYER UNKNOWN BATTLE GROUND (PUBG) MOBILE DI MEDAN BARU - rusliaman siahaan; Romindo Pasaribu; Bonifasius H Tambunan; Yosua M Sitorus (Journal of Economic and Business, 2021)
The purpose of this researc was to determine the effect of price perception and promotion on buying interest. The number of samples taken was 120 respondents, which purposive sampling method. Data collection was carried out by distributing questionnaires to the sample, namely Game Player Unknown Battle Ground (PUBG) Mobile in Medan Baru who had made purchases and used Unknown Cash (UC). The analysis technique chosen is the IBM SPSS Statistic 23 application. Based on the results of the analysis it was found that: 1) price perception has a positive and significant effect on buying interest in UC in PUBG Mobile Games in Medan Baru. 2) promotion has a positive and significant impact on buying interest in UC in the PUBG Mobile Games in Medan Baru. 3) price perception and promotion simultaneously influence buying interest in UC in PUBG Mobile Games in Medan Baru. In order for the PUBG Corporation to increase consumer buying interest, it is recommended that they provide appropriate prices and quality and increase promotions so that potential consumers are more familiar with and increase buying interest.